NEGOSIASI IDEOLOGI DALAM NOVEL KUBAH KARYA AHMAD TOHARI: ANALISIS HEGEMONI GRAMSCI - , MIRA TRI RAHAYU; , Dr. Supriyadi, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimed to identification ideology and analysis the ideology negotiation in Kubah. This research analyzed the marginalized communist people after G30S incident and the role of islam people in Indonesia. The idea of hegemony Gramsci used to analysis the dominant ideology and the powerless ideology in Kubah. The other else, the idea of hegemony Gramsci used to find the alternative hegemony which offered by author to the readers. This research showed that there were four ideologies in Kubah (communism, Islamism, humanism, and militarism). Every ideology supported the major idea of author which wanted to show the humanism aspects from Islamism after G30S incident. The alternative hegemony used as the negotiation medium to communist people. The other side, there were author criticismâs to critic the militarism of Orde Baru government. The criticisms were to critic the labeling as political prisoner, critic to hegemony in military, society, government regulations, religion aspect, and family. Based on this research could get conclusion that Kubah showed the marginalization of communist people after G30S incident. The marginalization was narrated by author by major character, Karman. The author whose has the background as islamist gave the alternative solution to the marginalization of communist people with humanism in Islamism precept. Keywords: Kubah, hegemony, Islamism, humanism, G30S